SELF-REGULATION AS A PREDICTOR OF STUDENT ACADEMIC ACHIEVEMENT IN ISLAMIC HIGHER EDUCATION - Mahfud; Muhammad Imamul Muttaqin Arisandi; Zainal Hakim; Abdulkarim Olatunji Abdulkadir (Institut Bahri Asyiq Galis Bangkalan, 2026)
The combination of religious science and science in the Islamic higher education curriculum requires students to manage the learning process autonomously as an essential prerequisite for academic success. This research intends to empirically examine the role of self-regulation capacity as a predictor of academic achievement of STAI Darul Hikmah Bangkalan students, Madura, Indonesia. Applying a quantitative approach with a correlational design, the study involved 180 students who were selected through proportionate stratified random sampling. Data were obtained using a self-regulation scale based on the theory of self-regulated learning which has been validated via expert judgment and Exploratory Factor Analysis (KMO = 0.84; factor loading 0.53–0.81; cumulative variance of 58.7%), as well as official documentation of GPA. The analysis was carried out with simple linear regression. The findings indicate that self-regulation significantly predicts academic achievement (B = 0.014; t = 6.875; p < 0.000). The determination coefficient (R² = 0.210) shows that self-regulation explains 21% of the variance in academic achievement a magnitude of the moderate-to-large effect according to Cohen's conventional guidelines. These findings confirm that the academic success of STAI Darul Hikmah students which carries out a dual curriculum and is rooted in the tradition of Islamic boarding schools is not solely supported by intellectual capacity, but is firmly predicted by the effectiveness of self-regulated learning (SRL) strategies enriched by Islamic values. As an implication, the strengthening of SRL-based academic guidance that consciously embeds the spiritual dimension is a necessity in order to produce independent, resilient, and competitive graduates.